2009
DOI: 10.1016/j.otohns.2009.05.027
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Reprocessing Techniques of Flexible Nasopharyngoscopes

Abstract: To provide assistance to otolaryngologists to decide the best manner in which to reprocess flexible nasopharyngoscopes, a review of existing English language medical literature regarding the methods of flexible endoscope reprocessing was performed, including previously published guidelines from other medical disciplines. Multiple steps were confirmed to be critical to effectively reprocess flexible nasopharyngoscopes. High-level disinfection has been determined to be the minimum level of disinfection required … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 10 publications
1
27
0
Order By: Relevance
“…Thus, an FFL would be considered a semicritical device and should undergo HLD between uses. HLD refers to the inactivation of pathogenic organisms such as viruses, mycobacteria, fungi, fungal spores, and if possible bacterial endospores …”
Section: Introductionmentioning
confidence: 99%
“…Thus, an FFL would be considered a semicritical device and should undergo HLD between uses. HLD refers to the inactivation of pathogenic organisms such as viruses, mycobacteria, fungi, fungal spores, and if possible bacterial endospores …”
Section: Introductionmentioning
confidence: 99%
“…However, mechanical cleaning, leak testing and use of enzymatic detergent are still recommended before the use of an AER (10,11). Other disadvantages of AERs are the high installation and maintenance costs (9,12). Despite these costs, a study comparing the cost effectiveness between AERs and chlorine dioxide wipes, showed that AERs were more cost effective in the long term (12).…”
Section: Discussionmentioning
confidence: 99%
“…Medical instruments are stratified by the Spaulding classification into three groups on the basis of level of disinfection required 1, 23.…”
Section: Discussionmentioning
confidence: 99%
“…Sterilization is a process by which all vegetative microorganisms and bacterial endospores are destroyed. Sterilization is required for all critical instruments based on the classification of Spaulding 1…”
Section: Discussionmentioning
confidence: 99%